0284 Occupational exposure and stroke – A critical review of shift work, and work-related psychosocial risk factors. (23rd June 2014) - Jakobsson, Kristina; Gustavsson, Per
Abstract : Objectives: Stroke is the third most common cause of death in developed countries, exceeded only by coronary heart disease and cancer, but there is still little knowledge on occupational risk factors. A systematic critical review was performed to assess the strength of evidence for causal associations between work-related psychosocial risk factors, shift work and stroke. Method: Literature on stroke incidence or mortality and occupational factors published up to 2012 was identified from Medline and other relevant databases. The 4 471 abstracts were evaluated independently by two reviewers. Six studies relevant to shift work and eight studies (among them four cohorts from Scandinavia) exploring job strain, job control or other job related "stress" exposures were identified. The evidence for an association was assessed according to defined criteria as strong, moderate, limited, or insufficient. Results: There is limited evidence for an association between shift work and stroke, mainly based on results from two occupational cohorts. There is also limited evidence for high job strain or low job control from cohort studies. Case- crossover studies, which would better reflect short-term effects, were lacking, and the only case-referent study found was very small. Conclusions: There is now fairly solid evidence that shift work and work-related psychosocial stress are risk factors for coronary heart disease; a fact that supports an association also with stroke, another cardiovascular disease. However, the epidemiological evidence for stroke is limited, with few studies, and very limited exposure information. Better study designs are needed to elucidate accumulated as well as triggering/short time effects.